2007
DOI: 10.1083/jcb.200704163
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of survival motor neurons (SMN) by PPM1G/PP2Cγ governs Cajal body localization and stability of the SMN complex

Abstract: The survival motor neuron (SMN) complex functions in maturation of uridine-rich small nuclear ribonucleoprotein (RNP) particles. SMN mediates the cytoplasmic assembly of Sm proteins onto uridine-rich small RNAs, and then participates in targeting RNPs to nuclear Cajal bodies (CBs). Recent studies have suggested that phosphorylation might control localization and function of the SMN complex. Here, we show that the nuclear phosphatase PPM1G/PP2Cγ interacts with and dephosphorylates the SMN complex. Small interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…Other studies involving dephosphorylation of SMN in the nucleoplasm, showed that PP1MG regulates SMN complex stability in CBs (Petri et al, 2007). Consistent with our findings, PP1MG activity is probably not altered in PP1c-depleted cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Other studies involving dephosphorylation of SMN in the nucleoplasm, showed that PP1MG regulates SMN complex stability in CBs (Petri et al, 2007). Consistent with our findings, PP1MG activity is probably not altered in PP1c-depleted cells.…”
Section: Discussionsupporting
confidence: 81%
“…There are sixteen potential phosphoserines in SMN. It will be interesting to determine whether PP1c targets the same residues as PP1MG and if not, this could explain why depletion of PP1MG decreases SMN localization to CBs (Petri et al, 2007), whereas PP1c depletion increases it.…”
Section: Discussionmentioning
confidence: 99%
“…SMN is a vital component in the cytoplasmic phase of snRNP biogenesis (Meister et al, 2002;Massenet et al, 2002), and might have a role analogous to its cytoplasmic functions in the CB by ensuring that nuclear snRNPs remain functional after a splicing reaction has taken place (Pellizzoni et al, 1998;Xu et al, 2005). Phosphorylation impacts SMN activity and localization (Grimmler et al, 2005;Petri et al, 2007). In particular, dephosphorylation of SMN by the nuclear phosphatase PPM1G is needed for SMN localization to CBs (Petri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation impacts SMN activity and localization (Grimmler et al, 2005;Petri et al, 2007). In particular, dephosphorylation of SMN by the nuclear phosphatase PPM1G is needed for SMN localization to CBs (Petri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor-2 (FGF-2) competes with gemin2 for binding to SMN and may regulate Cajal body formation [35]. The nuclear phosphatase PPM1G interacts with and dephosphorylates the SMN complex, and in a mechanism that involves unrip, is required to maintain SMN subcellular distribution and stability [36].…”
Section: Introductionmentioning
confidence: 99%